"Women Friendly" Spending? Welfare Spending and Women's Participation in the Economy and Politics. Issue 2 (25th October 2017) - Detraz, Nicole; Peksen, Dursun
Abstract : What effect do social welfare policies have on women's active involvement in the economy and politics? Though there is much policy and scholarly debate on a wide spectrum of socioeconomic and political outcomes of welfare spending, little research has explored the possible impact that social welfare policies have on one of the supposed major beneficiaries of such policies—women. Combining data on welfare spending in three areas—social security, health, and education—with data on women's labor force participation and share of seats in national legislatures, this article examines the extent to which welfare spending might affect women's economic and political status. The results from a panel of 97 countries for the years spanning 1990 to 2010 indicate that the government's fiscal commitment to social policies is positively related to female participation in the total labor force and national politics. The findings are robust to different model specifications, sample selection, and the use of instrumental variables. One major policy implication of the findings is that the government's fiscal commitment to key social welfare areas are likely to contribute to women's economic and political empowerment, which might in turn help address gender imbalances in the economy and political sphere.